2021
DOI: 10.1002/hec.4251
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alcohol sales restrictions on alcohol poisoning mortality: Evidence from Russia

Abstract: This paper examines the tough anti-alcohol legislation recently introduced in Russia, which due to regional variation allows it to be used as a natural experiment. The effect of the restricted trading hours on alcoholic poisoning mortality is estimated. To establish a causal link, difference-in-differences and synthetic controls are used. The main conclusion is that the sales restrictions lead to higher alcohol poisoning mortality, which implies that more toxic alcohol surrogates serve as substitutes for comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
3
0
1
Order By: Relevance
“…"Low" and "high" alcohol consumption are defined by whether a region's 1990 per capita consumption of pure ethanol was 11 There is some concern and evidence that higher prices and restrictions on legal alcohol sales might lead heavy drinkers to increase consumption of non-beverage alcohol surrogates. Skorobogatov (2021) tests for unintended effects of local strong alcohol sales hours restrictions on the consumption of surrogates using a difference-in-differences approach, exploiting varying hours restrictions introduced at different times across regions in 2005-2010. Results show that the mean hours restriction was associated with 16% higher alcohol poisoning mortality.…”
Section: Have Anti-alcohol Policies Reduced Deaths In Russia?mentioning
confidence: 99%
“…"Low" and "high" alcohol consumption are defined by whether a region's 1990 per capita consumption of pure ethanol was 11 There is some concern and evidence that higher prices and restrictions on legal alcohol sales might lead heavy drinkers to increase consumption of non-beverage alcohol surrogates. Skorobogatov (2021) tests for unintended effects of local strong alcohol sales hours restrictions on the consumption of surrogates using a difference-in-differences approach, exploiting varying hours restrictions introduced at different times across regions in 2005-2010. Results show that the mean hours restriction was associated with 16% higher alcohol poisoning mortality.…”
Section: Have Anti-alcohol Policies Reduced Deaths In Russia?mentioning
confidence: 99%
“…Material deprivation increased hazardous drinking as non-beverage alcohol was significantly cheaper 60 , 61 . Financial strain, especially among the elderly, might result in them producing and selling samogon as a means of diversifying their income, which increases the accessibility of samogon and reduces its market price due to the increased supply 62 , 63 . In addition, we found that hazardous alcohol consumption was higher among those male and female relatives who rarely communicated with their relatives—our survey informants.…”
Section: Discussionmentioning
confidence: 99%
“…This method combines the synthetic control method with IFE models and is less sensitive to small sample size than the traditional synthetic control method. It is being used by a rapidly growing literature using panel data models with U.S. county-level treatment (Cook, 2021;Cengiz and Tekgüç, 2018;Nguyen, 2020), or with treatment measured in similar smaller geographic areas in other countries (Skorobogatov, 2021;Mäkelä, 2017). As the GSC eliminates confounding factors that violate the identifying parallel trends assumption in event study designs, particularly for unemployment rate in our case, our use of the GSC provides causally interpretable results.…”
Section: Empirical Strategymentioning
confidence: 98%